Pengaruh Human Capital, Upah Minimum dan Angkatan Kerja terhadap Pertumbuhan Ekonomi Sektor Industri Pengolahan di Provinsi Jawa Tengah - Hari Winarto; Zumaeroh Zumaeroh; Diah Retnowati (Universitas Batanghari Jambi, 2022)
This study aims to analyze the effect of human capital, regional minimum wages and labor force on economic growth of the manufacturing sector in Central Java Province in 2011-2019. This type of research is quantitative. The research method uses multiple linear regression with panel data approach. The results showed that human capital and regional minimum wage have a positive and significant effect on the economic growth of the manufacturing sector in the province of Central Java. The labor force has not significant on the economic growth of the manufacturing sector in the province of Central Java. The implication of this finding is the need to improve the quality of human resources through increasing the number of scholarships. In addition, the need to increase the regional minimum wage.